Protective effect of silymarin on tacrolimus-induced kidney and liver toxicity - Funda Terzi; Mustafa Kemal Ciftci (BMC, 2022)
Abstract Background Tacrolimus (FK506) is an immunosuppressive agent and has toxic side effects such as nephrotoxicity, hepatotoxicity, and neurotoxicity. In our study, we aimed to investigate the protective effect of silymarin on renal and hepatic toxicity considered to be tacrolimus related. Methods In this 6-week experimental study, 46 eight-week-old healthy male rats were used. The groups comprised the Control (healthy rats, n = 6), Tac (tacrolimus 1 mg/kg, n = 8), silymarin 100 mg/kg (SLI 100 mg/kg n = 8), Tac + SLI 100 (tacrolimus 1 mg/kg + SLI 100 n = 8), SLI 200 (SLI 200 mg/kg n = 8), and Tac + SLI 200 (tacrolimus 1 mg/kg + SLI 200 mg/kg n = 8). After 6 weeks, all rats were sacrificed, and the tissue follow-up procedure was performed for kidney and liver tissues, histopathology, and in situ TUNEL analysis. Blood samples were analyzed for the total antioxidant capacity (TAC), total oxidant capacity (TOC), alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), albumin, total bilirubin, creatine. Results Histopathological findings of kidney and liver tissue of rats were determined to increase statistically in Tac group compared to SLI 1 00 and SLI 200 groups (P < 0.05). In addition, the Tac + SLI 100 and Tac + SLI 200 groups were found to be statistically similar to the Control group (P > 0.05). The in situ TUNEL method showed that the tacrolimus increased apoptosis while the silymarin decreased it. TOC levels increased statistically in Tac groups compared to silymarin-treated groups (P < 0.05). Although the TAC level was not statistically significant among the experimental groups (P > 0.05), the lowest was measured in the Tac group. The ALT, AST, GGT, total bilirubin, and creatine values were higher in the Tac group than in the silymarin groups (P < 0.05). There was no statistically significant difference between the groups with regard to the albumin level (P > 0.05). Conclusion In our study, we determined that tacrolimus caused damage to kidney and liver tissue. Histopathological, biochemical and apoptotic findings show that silymarin has a protective effect against nephrotoxicity and hepatotoxicity caused by tacrolimus.